Quality of Higher Education: A Bibliometric Review Study - Brika, Said Khalfa M.; Algamdi, Abdelmageed; Chergui, Khalil; Musa, Adam A.; Zouaghi, Rabia (Frontiers in Education, 2021)
This paper aims to analyse the literature review of the quality of higher education; the bibliometric analysis adapted using VOSviewer software to examine the data of 500 studies published in the Web of Science from 2000 to 2018 related to this topic. The results were presenting and discussed with the following approaches: (keywords, authors, references (research papers), research work, countries and research institutions). Finally, the paper concluded that Bibliometric analysis is fundamental in detailing the theoretical literature and developing an integrated theoretical framework on higher education quality.